Design, realisation and evaluation of a liquid hollow torso phantom appropriate for wearable antenna assessment. Issue 9 (20th June 2017) - Tsolis, Aris; Paraskevopoulos, Anastasios; Alexandridis, Antonis A.; Whittow, William G.; Chauraya, Alford; Vardaxoglou, John (Yiannis) C.
Abstract : This study examines the design, realisation and evaluation of a lightweight and low cost hollow oval cross‐section torso phantom appropriate for wearable antenna performance assessment. The phantom consists of an empty inner space (hollow) surrounded by a shell with double plastic walls between which there is a tissue simulating liquid. The phantom's plastic shell is made of a low loss cast acrylic and the liquid is a commercially available one with properties calibrated for the frequency range of 2–6 GHz. The proposed phantom is compared, through simulations, with a full liquid torso phantom and a heterogeneous anthropomorphic voxel phantom. In addition, the fabricated phantom is compared with human bodies and a homogeneous anthropomorphic solid phantom, through measurements. The phantom performance is tested in terms of electric field distribution of a wearable antenna on its surface and the path loss between two wearable antennas, on either side of the phantom. It is proved that the hollow phantom performance approximates the full liquid phantom when an RF absorbing material is placed in the central hollow region. The phantom performance in terms of S 11 wearable antenna measurements is evaluated and found in good agreement with real human bodies in the examined frequency range (2–6 GHz). The far‐field wearable antenna performance of the proposed phantom shows deviation in gain <1.5 dB, compared with anthropomorphic phantom.